California's first year with local control finance and accountability - David Menefee-Libey; Charles Taylor Kerchner (Arizona State University, 2015)
In 2013, Governor Jerry Brown and the California legislature radically restructured the state's school funding system and accountability systems with a weighted student formula and a mandated local planning process in each district. The new law substitutes local politics and grassroots agency for state-driven mandates and compliance reviews. While the Local Control Funding Formula has had immediate impact, early evaluations suggest that districts like the new system and are earnest in their implementation efforts, but it will take years to assess the effect of the multi-indicator Local Control Accountability Plans. Simultaneously, the state is implementing the Common Core State Standards and the associated Smarter Balanced Assessment Consortium tests, which make creating local accountability plans more complicated.